The extracellular chaperone clusterin potently inhibits human lysozyme amyloid formation by interacting with prefibrillar species. - Kumita, JR; Poon, S; Caddy, G; Hagan, C; Dumoulin, M; Yerbury, J; Stewart, E; Robinson, C; Wilson, MR; Dobson, C (2007)
We have studied the effects of the extracellular molecular chaperone, clusterin, on the in vitro aggregation of mutational variants of human lysozyme, including one associated with familial amyloid disease. The aggregation of the amyloidogenic variant I56T is inhibited significantly at clusterin to lysozyme ratios as low as 1:80 (i.e. one clusterin molecule per 80 lysozyme molecules). Experiments indicate that under the conditions where inhibition of aggregation occurs, clusterin does not bind detectably to the native or fibrillar states of lysozyme, or to the monomeric transient intermediate known to be a key species in the aggregation reaction. Rather, it seems to interact with oligomeric species that are present at low concentrations during the lag (nucleation) phase of the aggregation reaction. This behavior suggests that clusterin, and perhaps other extracellular chaperones, could have a key role in curtailing the potentially pathogenic effects of the misfolding and aggregation of proteins that, like lysozyme, are secreted into the extracellular environment.